Protease sensitivity and redistribution of CD71 and glycophorin A on K562 cells - Yu, C-H.; Wang, H.; Wang, Y.; Cui, N-X.; Zhao, X.; Rong, L.; Yi, Z-C. (Cellular and Molecular Biology, 2017)
Transmembrane proteins are delivered to plasma membrane from the endoplasmic reticulum and Golgi complex by vesicular transport along with the cytoskeletal network. Disruption of this process likely affects transmembrane protein expression. K562 cells were digested with Streptomyces griseus protease for different periods of time, and then re-cultured with different cytoskeletal and glycosylation inhibitors. Cell viability and surface expression of transferrin receptor (CD71) and glycophorin A (GPA) were analyzed before and after re-culture by flow cytometry. We found that digestion with protease almost completely removed extracellular CD71 and GPA but their expression recovered to the initial levels after re-culture for 8 h and 24 h, respectively. The microtubule depolymerizer colchicine promoted cell surface recovery of CD71 but inhibited that of GPA; the microtubule stabilizer paclitaxel inhibited cell surface recovery of CD71 but promoted that of GPA; the microfilament depolymerizer cytochalasin D had no effect on cell surface recovery of CD71 and GPA; the microfilament stabilizer phalloidin inhibited cell surface recovery of GPA. The glycosylation inhibitor tunicamycin inhibited the recovery of both CD71 and GPA, and BADGP inhibited the recovery of GPA. These studies show differential sensitivities of surface proteins on K562 cells to proteases, and suggest molecular mechanisms of transmembrane protein transport and cycling.